Single dose trypanocide surveillance of diminazene aceturate on mice infected by trypanosoma - Lazuardi, Mochamad (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2005)
Diminazene aceturate is one of a limited number compounds currently market for treatment infection cases of infection blood eucaryot parasits llike a Leishmania, and Trypanosoma The research design of this research was post test only control groups design for founding single therapeutics dose of the eukariyot parasite blood. The serial range dose of this research was used at 1,5 to 4 mg/kg bw by intraperitoneal administreted to infected mice (Mus musculus albinus) of the Trypanosoma evansi Bangkalan isolates. The result of this research showed the minimum single therapeutics dose at 3,5 mg/kg bw (p